REVITALISASI ETIKA REMAJA LABUHANBATU: ANALISIS SEMIOTIKA TARI PILANDOK TAKIAL-KIAL SEBAGAI PEDOMAN PERILAKU - Tri Rahma Dana; Andra Maulana Syachrendra; Adib Alriansyah; Andini Eka Syafitri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to explore the pedagogical values within the Pilandok Takial Kial dance as an instrument for revitalizing youth ethics in Labuhanbatu Regency. In the digital era, teenagers face challenges of moral degradation and identity crisis that distance them from their local cultural roots. This study employs a qualitative approach with descriptive-analytical methods using Roland Barthes' Semiotic theory. Data were collected through textual observation of movements, literature studies, and in-depth interviews with dance maestros and traditional leaders. The results show that the Pilandok dance is not merely an aesthetic representation of a mousedeer’s movements but a system of signs containing strategic moral messages. Symbols of vigilance (eyes), resilience (takial-kial feet), and manners (worship gestures) are manifestations of the "civilized ingenuity" concept. The implications of this study emphasize the importance of integrating dance philosophy into character education curricula to shape a Generation Z that is intellectually bright yet still upholds Malay values of politeness. Keywords: Pilandok Takial Kial Dance, Semiotics, Youth Ethics, Labuhanbatu, Cultural Revitalization.   Abstrak: Penelitian ini bertujuan untuk mengeksplorasi nilai-nilai pedagogis dalam Tari Pilandok Takial Kial sebagai instrumen revitalisasi etika remaja di Kabupaten Labuhanbatu. Di era digital, remaja menghadapi tantangan degradasi moral dan krisis identitas yang menjauhkan mereka dari akar budaya lokal. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analitis melalui teori Semiotika Roland Barthes. Data dikumpulkan melalui observasi tekstual gerak, studi literatur, serta wawancara mendalam dengan maestro tari dan tokoh adat. Hasil penelitian menunjukkan bahwa Tari Pilandok bukan sekadar representasi estetika gerak kancil, melainkan sebuah sistem tanda yang mengandung pesan moral strategis. Simbol kewaspadaan (mata), resiliensi (kaki takial-kial), dan adab (gestur sembah) merupakan manifestasi dari konsep "kecerdikan beradab". Implikasi penelitian ini menekankan pentingnya integrasi filosofi tari ke dalam kurikulum pendidikan karakter untuk membentuk Generasi Z yang cerdas secara intelektual namun tetap menjunjung tinggi nilai kesantunan Melayu. Kata kunci: Tari Pilandok Takial Kial, Semiotika, Etika Remaja, Labuhanbatu, Revitalisasi Budaya.